EFEKTIVITAS ALAT TANGKAP MINI PURSE SEINE MENGGUNAKAN SUMBER CAHAYA BERBEDA TERHADAP HASIL TANGKAP IKAN KEMBUNG (Rastrelliger sp.) - Ifa Nur Rosyidah; Akhmad Farid; Apri Arisandi (Jurnal Kelautan, 2009)
In fish catching activity, the fishermen in Banyuanyar district use mini tools for catching fish (purse seine) and use light assist tools for an operation in the night day. The light, that is used, is kerosene pressure lantern and mercury lights or lamp that is used on water surface (surface lamp). This kind of light is used to collect “pelagic” fish that has positive phototaxis characteristic. Puffer fish’s response towards different sourse of light, that’s kerosene pressure lantern and mercury light is needed to be known. Therefore, we can know the source of light that is more effective in order to collect the fish. It is hoped that the productivity of puffer fish will be developed for the fishermen. During the research with ten times repeating, the total account of puffer fish’s haul that is resulted with two different treatment  by using kerosene pressure lantern and mercury light is that 810 kg and 1.460 kg. The data of puffer fish’s haul that is gotten after using Mann-Whitney test shows that the kerosene pressure lantern and mercury light not to really different, especially in the haul of puffer fish in significant standart (0,05) is 2,262, while in Mann-Whitney test account is 0,171. That means the fishermans in Banyuanyar can use kerosene pressure lantern and mercury light for catching fish as the light assist tools for an operation in the night day. Keywords     :   Purse Seine, Mercury Light and Kerosene Pressure Lantern, Puffer Fish (Rastrellinger sp.).